The upside of anger - Binder, Mike, 1958-; Gartner, Alex.; Lee, Sammy; Allen, Joan, 1956-; Costner, Kevin; Christensen, Erika, 1982-; Wood, Evan Rachel, 1987-; Russell, Keri, 1976-; Witt, Alicia, 1975-; New Line Cinema Corporation; Media 8 Entertainment (Firm); New Line Home Entertainment (Firm); et al. ([United States] : New Line Home Entertainment ; Burbank, CA : Distributed by Warner Home Video, 2005)
Terry Wolfmeyer is a sharp-witted suburban wife who is left alone to raise her four headstrong daughters when her husband unexpectedly disappears. Things get even more hectic around their house when Terry falls for her neighbor Denny, a once-great baseball star turned local radio D.J. This leaves her daughters out on a limb because now they have to juggle their own romantic ups and downs as well as having to deal with the dilemmas of their mom.
DVD release of the 2005 motion picture.
Special features: commentary with director Mike Binder, Joan Allen, and moderated by filmmaker Rod Lurie ; deleted scenes with commentary by director Mike Binder ; 30-minute documentary ; theatrical trailer.
Director of photography, Richard Greatrex ; art director, Tim Stevenson ; editors, Steve Edwards, Robin Sales ; music, Alexandre Desplat ; costume designer, Deborah Scott ; production designer, Chris Roope.
Joan Allen, Kevin Costner, Erika Christensen, Evan Rachel Wood, Keri Russell, Alicia Witt, Mike Binder.
MPAA rating: R; for language, sexual situations, brief comic violence and some drug use.
DVD ; region 1 ; widescreen (2.35:1) presentation ; Dolby Digital 5.1 surround, Dolby Digital 2.0 stereo.
Keywords: Single-parent families -- Drama; Man-woman relationships -- Drama; Disc jockeys -- Drama; Madre e hijos -- Teatro; Feature films; Video recordings for the hearing impaired; Romance -- Feature; Comedy -- Feature; Family -- Feature